Rahn Emas Dalam Fatwa Majelis Ulama Indonesia (Studi Analisis Fatwa Nomor 26 Tahun 2002 Tentang Rahn Emas) - Suprapdi Suprapdi; Ismi Lathifatul Hilmi (Universitas Nurul Jadid, 2023)
MUI Fatwa Number 26 of 2002 concerning Rahn Emas with the issue of the permissibility of combining two contracts in one transaction which gave rise to several disagreements by Indonesian Muslim scholars, because the fatwa allows hybrid contracts or a combination of qardh and ijarahcontracts. A qardh contract occurs when the LKS provides a loan to a customer with gold as collateral, while an ijarah contract occurs when the LKS rents out a gold storage box and collects wages from the ijarah contract. This type of article is library research, where data collection is through books, official websites, and journals. The approach used is normative syar'i which is based on the Al-Qur'an and Hadith as well as other Islamic laws. Based on the legal basis used, MUI uses four basic arguments, namely the Qur'an, Hadith, Ijma', and the Rules of Fiqh. Based on this legal basis, the use of Rahn Emas is permissible until there is an argument against it and when a Rahn Emas contract is entered into, the maintenance cost clause is included in the contract. The merging of two contracts in one contract is used as a murakkab (multi-contract) contract, the murrakab contract here is included in the al-'uqud al-mujtami'ah group. So, in the practice of multi-contract transactions, it can be seen that the law of origin of multi-contract transactions is permissible, unless there is evidence forbidding it, and as long as it does not cause things that are forbidden such as usury, price uncertainty, fraud, and so on. The reason for issuing the Fatwa is to provide legal clarity in transactions using Rahn Emas contract products that comply with Sharia principles.Keywords: Fatwa, Mui, Rahn Emas.